1987
DOI: 10.1111/j.1365-2044.1987.tb05314.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying and small bowel transit times in volunteers after intravenous morphine and nalbuphine

Abstract: Summary Gustrii. emptying halfltinie.y and small intestinal transit times were measured in a double Key wordsAnulgesics, narcotic; morphine. nalbuphine. Gastrointestinal truct; stomach, intestine.Opioid drugs depress gastrointestinal function but there is little information on quantitative differences bctwccn agonists such as morphine and newer synthetic agonist-antagonist drugs. It would be of clinical importance to be able to predict the type and duration of the effect of each drug administered for pain reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(16 citation statements)
references
References 11 publications
1
13
0
2
Order By: Relevance
“…It can also be speculated that morphine decreases gastrointestinal transit and the slowing down of gut motility facilitates bacterial translocation. Data in support of this hypothesis are provided by studies that show treatment with chronic morphine alone resulted in a significant increase in the concentration of serum endotoxin (Yukioka et al 1987;Runkel et al 1993). In other animal experimental models, morphine has been shown to not only induce the degradation of the host defense barrier but also potentiate the effects of LPS (Roy et al 1998b,c;Ocasio et al 2004).…”
Section: Morphine and Susceptibility To Infectionmentioning
confidence: 76%
“…It can also be speculated that morphine decreases gastrointestinal transit and the slowing down of gut motility facilitates bacterial translocation. Data in support of this hypothesis are provided by studies that show treatment with chronic morphine alone resulted in a significant increase in the concentration of serum endotoxin (Yukioka et al 1987;Runkel et al 1993). In other animal experimental models, morphine has been shown to not only induce the degradation of the host defense barrier but also potentiate the effects of LPS (Roy et al 1998b,c;Ocasio et al 2004).…”
Section: Morphine and Susceptibility To Infectionmentioning
confidence: 76%
“…It has subsequently been shown that morphine delays gastrointestinal (GI) transit in the mouse and the rat [28], as well as in humans [29,30]. We have shown that C3HeB/FeJ mice implanted with slow-release morphine pellets, or with osmotic mini-pumps dispensing morphine, decrease intestinal transit [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies demonstrated that mice implanted with morphine pellets are sensitized to oral Salmonella enterica , serovar Typhimurium acute infection, where potentiating effect is dependent on the MOR (Feng et al, 2006a; Breslow et al). Interestingly, some studies also indicated that morphine treatment alone results in a significant increase in the concentration of serum endotoxin and may be able to induce sepsis in mice, which suggests that morphine can modulate the gut-associated immune system (Yukioka et al, 1987). In other animal experimental models, morphine has been shown not only to induce the degradation of the host defense barrier but also synergize with LPS and augment the secretion of both IL-6 and TNF-α (Roy et al, 1998c; Ohara et al, 2005; Ocasio et al, 2004).…”
Section: Morphine and Susceptibility To Infectionmentioning
confidence: 99%